A digital approach to dynamic jaw tracking using a target tracking system and a structured-light three-dimensional scanner. Issue 1 (January 2019) - Kwon, Joo Hyun; Im, Sungbin; Chang, Minho; Kim, Jong-Eun; Shim, June-Sung
Abstract: Purpose: This technical procedure describes a method for tracking mandibular movement using a three-dimensional (3D) optical scanner and target tracking system to digitally portray the motion of the mandible and temporomandibular joints by merging cone beam computed tomography (CBCT) data. Methods: Four nonreflective targets were attached to the labial surface of the incisors in a noncolinear arrangement. Mandibular movement was tracked directly using a 3D facial scanner and target tracking software after merging facial scanning data, digital data obtained from a diagnostic cast, and CBCT scan data based on several landmarks of the anterior teeth. The moving path of the subjects' mandible was converted to CBCT-based data to confirm the actual movement of the mandible and temporomandibular joints. Conclusions: The digital implementation of mandibular movement using a 3D optical scanner and target tracking system is not prone to the same restrictions and limitations inherent in mechanical equipment; therefore, it is possible to reconstruct more realistic movement(s). This technique can be used in a wide variety of dental applications involving movement of the mandibular jaw, such as fabrication of dental prostheses, or for the diagnosis and treatment of temporomandibular joint disease.